2008
DOI: 10.1007/s00127-008-0358-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to care and treatment delays in first and multi episode psychosis

Abstract: Pathways to care in this treatment setting correspond more to findings from first world and newly industrialized countries. A subgroup of multi episode patients had very long periods of untreated illness. Limitations include small sample size and the retrospective nature of data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 46 publications
3
46
1
3
Order By: Relevance
“…Mindful of overgeneralizations, which might ignore the uniqueness of mental health services in Africa, we note that our findings on first contact or THP/DUP relationship are consistent with previous South African (Mkize et al, 2004; Temmingh et al, 2008) and African-studies (Abiodun, 1995; Gureje et al, 1995; Gureje et al, 2006; Odinka et al, 2014; Patel et al, 1997). However, caution against causal inference or interpretation of the benefit/risk of specific types of first contact service provider (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Mindful of overgeneralizations, which might ignore the uniqueness of mental health services in Africa, we note that our findings on first contact or THP/DUP relationship are consistent with previous South African (Mkize et al, 2004; Temmingh et al, 2008) and African-studies (Abiodun, 1995; Gureje et al, 1995; Gureje et al, 2006; Odinka et al, 2014; Patel et al, 1997). However, caution against causal inference or interpretation of the benefit/risk of specific types of first contact service provider (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 14 studies identified in the review, two were conducted in Ethiopia [20, 21], eight in Nigeria [2229], three in South Africa [30–32] and one in Zimbabwe [33]. They consisted of the following populations: 11 had adult patients, one had adult caregivers of persons with mental disorders [30], one with both children and adults [20], and one with children and adolescents [27].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, four studies examined the association between consulting traditional or religious healers as first provider and experiencing relative delays in accessing mental health services. All were conducted in populations with first-episodes of mental disorders, mainly first-episode psychosis [20, 26, 29, 32], and reported longer delays in accessing mental health services where traditional or religious healers were the initial care providers.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate aim shall be that of making scientifically sound, acceptable, and affordable care accessible to patients. Various attempts have been made to study the pathway to care for dementia, alcohol use disorders,[11] psychiatric morbidity[12] acute renal colic,[13] post-natal depression,[14] Attention Deficit Hyperactivity Disorder (ADHD)[15] etc.…”
Section: Discussionmentioning
confidence: 99%